Introduction to the Theme Issue: The Iron Cage Unchained: Christian Perspectives on Business in the Post-Modern Age - Wong, Kenman L. (Christian scholar's review, 2008)
Max Weber lamented over a century ago that the context in which industrial age economic organizations operate emphasizes a technical and cultural rationalization focusing on the material at the expense of the super-material. The pursuit of material rewards in the modern economy has left little room for a spiritual or theological approach to understanding work and business. More recently, scholars and practitioners have begun to focus attention on the tremendous human and ecological costs of myopic materialism, and there appears to be growing interest in the secular business academy in both alternative foundations for capitalism, business and organizations, including spiritually grounded ones.